Hubungan Penerapan Metode One Day One Ayat dengan Kemampuan Menghafal Al-Qur’an pada Siswa: The Relationship of Applying the One Day One Verse Method with the Ability to Memorize the Qur'an in Students - Rubiyad, Adib; Khovivatun Nazah, Siti; Qodir, Abdul (ISEDU : Islamic Education Journal, 2023)
The "One Day One Ayat" method is suitable for children in early childhood education (PAUD), kindergarten (TK), and elementary school (SD), especially for beginners in memorizing the Quran. With this method, children find it easier and faster to memorize the Quran, experiencing enjoyment rather than feeling burdened. They do not face difficulties in memorization since they only need to memorize one verse per day. This research adopts a quantitative approach using the correlational method, which aims to identify the relationship between variables. The sampling technique involves the use of questionnaires and tests, with the population consisting of 40 students at SDIT Insan Ulul Albaab Perum Villa Balaraja Desa Saga. The results indicate a correlation between the "One Day One Ayat" method and the ability to memorize the Quran.